The evolution of morals under indirect reciprocity - Alexia Gaudeul; Claudia Keser; Stephan Müller (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
We study the coexistence of strategies in the indirect reciprocity game where agents have access to second-order information. We fully characterize the evolutionary stable equilibria and analyze their comparative statics with respect to the cost-benefit ratio (CBR). There are indeed only two stable sets of equilibria enabling cooperation, one for low CBRs involving two strategies and one for higher CBR's which involves two additional strategies. We thereby offer an explanation for the coexistence of different moral judgments among humans. Both equilibria require the presence of second-order discriminators which highlights the necessity for higher-order information to sustain cooperation through indirect reciprocity. In a laboratory experiment, we find that more than 75% of subjects play strategies that belong to the predicted equilibrium set. Furthermore, varying the CBR across treatments leads to changes in the distribution of strategies that are in line with theoretical predictions.
Keywords: C73; C91; D83; 330; Indirect reciprocity; Cooperation; Evolution; Experiment